Optimal Operation of the Water-lifting Unit in Determining the Water Flow in the Water Source. (2016) - Kushnir, V.; Benyukh, O.; Kushnir, A.
Abstract: It contains some features due to the peculiarities of use of the mechanized water-lifting equipment on the pasture. A variety of devices used for mechanization of water lifting on pastures can be explained by different types of intakes, deep wells, source water flow rate as well as the by the search for effective water-pump designs. The analytical research of a water flow to a shallow pit well was made. It was established, that inside the unconfined aquifer the change of well output depending on depth of water layer is defined by a graph, which is close to parabola. The equations obtained allow us to determine the dynamic water level in the well for any length of time of the source use.